A multi-target therapeutic strategy: The efficacy of coffea canephora husk extract in mitigating oxidative stress, infection, and inflammation – a systematic review - Kamilah, Rona Hawa; Palungan, Juliana (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Robusta coffee (Coffea canephora) husk is a massive agro-industrial by-product. Despite possessing a rich phytochemical profile superior to Arabica, it remains underutilized as environmental waste. This review explores its valorization from a pollutant into a functional pharmaceutical resource. Purpose: To synthesize evidence regarding the bioactive potential of Robusta husk as a